Determinación de la función biológica y toxicidad del extracto de tres plantas silvestres (Petiveria Alliacea, Plectranthuns Amboinicus y Plantago Major) - Demera Lucas, Washington Fernando (2023)
The main objective of this research was to determine the biological function and toxicity of the extract of three wild plants (Petiveria alliacea, Plectranthuns amboinicus and Plantago major) and to verify the presence of bioactive compounds that are used in the elaboration of functional foods. A completely randomized design (DCA) was applied in a bifactorial arrangement AxB, six treatments with four replicates each were studied. In the determination of alkaloids, the Dragendorff test was used and in the case of tannins, the ferric chloride test, in addition, the DPPH methodology was used in the antioxidant activity at concentrations of 200 ppm in the extracts of Plectranthus amboinicus and Plantago major, and 400 ppm for Petiveria alliacea. The absence of alkaloids (-) was obtained in the three extracts, while the Plectranthus amboinicus extract had the highest tannin content (+++) followed by the Plantago major extract (++) and the absence of the Petiveria alliacea extract (-). Regarding antioxidant activity, it presented an average of 114,845 µmol Equivalent to Trolox /g of dry sample for Plectranthus amboinicus, 23,249 in Plantago major, and 14,936 in Petiveria alliacea. The extract that showed the best qualities was Plectranthus amboinicus both in percentage of tannins and antioxidant activity. All the extracts presented a low toxicity value, because they require high concentrations to have a 50% inhibition.